Exploring Research Trends of Physics Concept Mapping in Physics Learning: Bibliometric Analysis - Putri Lintang Utami; Nadi Suprapto; Hasan Nuurul Hidaayatullaah (Studies in Philosophy of Science and Education, 2022)
Research related to the application of concept mapping in physics learning is increasing and has become a trending topic for decades. This research purpose are (1) Analyze the research network and visualization concept mapping research in physics learning and contributions to learning physics (2) Analyze contribution of Indonesian Researchers on Concept mapping research (3) Analyze research recommendations related to concept mapping in physics learning. This bibliometric analysis using Scopus database in 2012-2023 period documents and analyze by VOSviewer. Visualization results with physics concept mapping be found in 6 clusters with the dominant items are mapping, students, and physics. The implementation of concept mapping in physics learning has many impact there are conceptual understanding, student performance, learning outcome, problem solving and physics misconception. Indonesia has contribute in physics concept mapping research with Universitas Negeri Manado being the most productive affiliations, Polukan c. being the most productive author and the most cited publication is “The effectiveness of Concept Mapping Content Representation Lesson Study (ComCoReLS) model to improve skills of Creating Physics Lesson Plan (CPLP) for pre-service physics teacher”. Based on network visualization the research recommendation about physics concept mapping are about concept mapping’s research in problem solving and misconceptions.